Bank efficiency and the bond markets: Evidence from the Asia and Pacific region - Donghyun Park; Shu Tian; Qiongbing Wu (Asian Development Bank (ADB), 2020)
This study examines the impact of bond markets on both bank profit and cost efficiency. By employing the stochastic frontier approach and utilizing a large micro dataset for 926 banks covering 27 economies from the Asia and Pacific region over the period from 2004 to 2017, we find that both the bond market development and bond market structure are relevant to bank efficiency. The development of bond markets generally has a positive (negative) effect on bank profit (cost) efficiency. Given the development level of the aggregate bond market, increasing the proportion of corporate bonds will enhance both bank profit and cost efficiency. Moreover, given the development level of a country's corporate bond market, a greater share of local currency corporate bonds is significantly and positively related to both bank profit and cost efficiency. In addition, increasing share of bank-issued corporate bonds in corporate bonds significantly increases (decreases) bank profit (cost) efficiency. Overall, our results point to the significant importance of local currency corporate bonds to the overall bank efficiency. Our findings provide important implications for both policy makers and bank management.
Keywords: D20; G21; G28; 330; Asia and Pacific region; bank efficiency; bond market development; bond market structure; stochastic frontier analysis